Hubungan Body Image dengan Kecemasan Sosial pada Mahasiswi Pengguna Instagram - Cindy Claudia; Dini Syah Fitri; Diva Ayunda Tobing; Ghefira Wahyu Tsuraya; Raudhahtul Jannah; Vania Putri Saecan; Silvi Juwita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to analyze the relationship between body image and social anxiety among female university students who use Instagram. Using a quantitative approach with a correlational design, the study involved 65 female students selected through random sampling. Data were collected via an online questionnaire with Likert-scale instruments to measure body image and social anxiety. The analysis results using Pearson's Product Moment test showed a negative but insignificant relationship between body image and social anxiety. These findings suggest that a positive body image is associated with lower levels of social anxiety, while dissatisfaction with body image tends to increase social anxiety. The limitations of this study lie in the sample size and the limited variables considered, which may affect the generalizability of the results.